Bisakah Bank Muamalat Indonesia Menghindari Kesulitan Keuangan? Sebuah Investigasi Teori Model Springate - Rafiqi, Iqbal; Afifah Nadhirah; Faizah, Maftuhatul (Universitas Negeri Surabaya, 2025)
Previous studies on financial distress in Islamic banking have tended to use broad samples. In contrast, this research specifically analyses the potential for financial distress at Bank Muamalat Indonesia, a leading Islamic bank which has recently undergone restructuring. The main objective is to examine how four financial ratios — Return on Assets (ROA), Return on Equity (ROE), Operational Costs to Operating Income (BOPO) and Financing to Deposit Ratio (FDR) influence the bank's financial distress. Additionally, the Springate Model is applied to predict the bank's financial distress during the period from 2016 to 2022, providing dual validation for the findings. A descriptive quantitative methodology was employed, with data sourced from Bank Muamalat Indonesia's quarterly financial statements. Multiple regression analysis indicates that the four financial ratios have no significant effect on financial distress, either partially or simultaneously (p-value > 0.05). Furthermore, analysis using the Springate Model is consistent with these findings. During the observation period, Bank Muamalat Indonesia's S-score consistently remained above 0.862, indicating healthy and stable financial conditions and suggesting that the bank is not predicted to experience financial distress